The relationship between professional and universal ethics of engineers - Mat, Zawiah; Sulaiman, Nooraini; Arif, Sazelin; Sidek, Safiah; Ismail, Norain; Basir, Siti Arni (Gyandhara International Academic Publications, 2018)
Purpose: The aim of this study is to identify the relationship between professional and universal ethics of engineers. Methodology:This study used quantitative methods to distribute the questionnaire by using random sampling to get data from 248 respondents of engineers from government and private sectors in Melaka. Respondents were required to valuate agreement to statement about work ethics that used a five-point Likert scale. Meanwhile, the scales used for measuring correlation were given as 0.000-0.2000 “negligible”, 0.201-0.400 “low”, 0.401-0.600, “moderate”, 0.601-0.800 “high”, and 0.801-1.000 “very high”. The Pearson correlation analysis was used to obtain these correlation results. In this research, we analysed the data collected using SPSS Ver.22 to identify the relationship between professional and universal ethics of engineers in Melaka. Main Findings:The findings showed that all variables of professional of engineers correlated significantly with universal ethics. The significant level (p-value) was found to be less than 0.05, the study findings indicate a significant relationship between independent variables and dependent variable. Results obtained in this study confirmed that there were significant positive relationships between all variables that could influence professional and universal ethics. Implications:This study contributes towards the improvement of Board of Engineers Malaysia (BEM’S) existing policy. Based on the study’s findings, the policy implication of this study includes: responsible bodies such as the governing institutions of engineers need to ensure that ethical practices are made as the main core in their profession by increasing knowledge and awareness about ethical practices in the engineering profession. Originality:This study only focus on the relationship between professional and universal ethics of engineers and the results will be useful towards the improvement of Board of Engineers Malaysia (BEM’S) existing policy.